Unveiling the Evolutionary Lineages and Habitat Dynamics of the Monotypic Crowned River Turtle Hardella thurjii (Gray, 1831) (Testudines: Geoemydidae): Strategic Conservation Insights for an Endangered Freshwater Turtle From Southern Asia - Imon Abedin; Arunima Singh; Jayaditya Purakayastha; Shailendra Singh; Kulendra Chandra Das; Hyun‐Woo Kim; Hye‐Eun Kang; Shantanu Kundu (Ecology and Evolution)
ABSTRACT The matrilineal evolutionary history and habitat preferences of the monotopic freshwater turtle Hardella thurjii remain largely unexplored, posing challenges for the development of precise and effective conservation strategies. This study provides the first complete mitochondrial genome sequence of H. thurjii (16,699 bp), encompassing 13 protein‐coding genes (PCGs), 22 transfer RNAs, two ribosomal RNAs, and an AT‐rich control region (CR). Most PCGs are initiated by ATG, except for cytochrome c oxidase subunit I gene (COI), which uses GTG, with eight PCGs having complete termination codons and five exhibiting incomplete stop codons. The CR of H. thurjii exhibits a distinctive structural organization, characterized by conserved sequence blocks and three consensus tandem repeats, distinguishing it from other Batagurinae species. The phylogenetic analyses based on Bayesian inference and maximum‐likelihood approaches using PCGs reveal a sister relationship between H. thurjii and other Batagur species, further corroborating the monophyletic status of the subfamily Batagurinae. Further, species distribution modeling with an ensemble approach effectively maps the global habitat suitability of H. thurjii for conservation planning under current and future climates. The model identified 110,490 km2 of suitable habitat in the present scenario, with 35,757 km2 in the eastern range and 83,723 km2 in the western range. Notably, future climate projections indicate a 32.38% overall increase in suitable habitat, primarily in the eastern range, while the western range faces a decline in habitat suitability. This contrasting pattern altered habitat geometry dynamics, increasing the size, number, and connectivity of patches in the eastern range while reducing and fragmenting them in the western range. By integrating mitogenomic and habitat suitability analyses, this study offers valuable insights into the past evolutionary history and current ecological preferences of endangered H. thurjii , aiding the development of effective conservation and management strategies for this species and other freshwater turtles globally.